Odpowiedzi

Najlepsza Odpowiedź!
2009-11-15T12:42:17+01:00
Po przekształceniu:
y=-2x+6
-3y=-x+10 mnożymy razy -2

y=-2x+6
6y=2x-20 zatem:

y-6y=-14
-5y=-14
y=2,8

2,8=-2x+6
2x=3,2
x=1,6
A=(1,6;2,8)
2009-11-15T12:47:56+01:00
2x+y-6=0
2x-6=-y /*(-1)
6-2x=y

dajmy że:
- x=2 to y=6-2*2=2 x=2 y=2
- x=3 to y=6-2*3=0 x=3 y=0

x-3y-10=0
-3y-10=-x /*(-1)
3y+10=x

dajmy że:
- y=1 to x=3*1+10=13 x=13 y=1
- y=2 to x=3*2+10=16 x=16 y=2

na podstawie tych danych robisz linie na osi współrzędnych i przecinają się one w (4, -2)